A Coating‐Free Nonfouling Polymeric Elastomer. Issue 31 (16th June 2017) - Hung, Hsiang‐Chieh; Jain, Priyesh; Zhang, Peng; Sun, Fang; Sinclair, Andrew; Bai, Tao; Li, Bowen; Wu, Kan; Tsao, Caroline; Liu, Erik J.; Sundaram, Harihara S.; Lin, Xiaojie; et al.
Abstract : Medical devices face nonspecific biofouling from proteins, cells, and microorganisms, which significantly contributes to complications and device failure. Imparting these devices with nonfouling capabilities remains a major challenge, particularly for those made from elastomeric polymers. Current strategies, including surface coating and copolymerization/physical blending, necessitate compromise among nonfouling properties, durability, and mechanical strength. Here, a new strategy is reported to achieve both high bulk mechanical strength and excellent surface nonfouling properties, which are typically contradictory, in one material. This is realized through a nonfouling polymeric elastomer based on zwitterionic polycarboxybetaine derivatives. By hiding both charged moieties of the zwitterionic compounds with hydrocarbon ester and tertiary amine groups, the bulk polymer itself is elastomeric and hydrophobic while its superhydrophilic surface properties are restored upon hydrolysis. This coating‐free nonfouling elastomer is a highly promising biomaterial for biomedical and engineering applications. Abstract : A stable nonfouling polymeric elastomer is demonstrated. This elastomer, based on zwitterionic polycarboxybetaine derivatives, requires no hydrophilic surface coating to achieve excellent nonfouling surface properties. By hiding both charged moieties of the zwitterionic compounds, a hydrophobic elastomer is fabricated; hydrolysis of its outermost surface then restores superhydrophilic and nonfouling surface properties, while maintaining excellent bulk mechanical characteristics.